2021
DOI: 10.3390/ijms221910772
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Photomorphogenic 1 Enhances ER Stress Tolerance in Arabidopsis

Abstract: Interaction between light signaling and stress response has been recently reported in plants. Here, we investigated the role of CONSTITUTIVE PHOTOMORPHOGENIC 1 (COP1), a key regulator of light signaling, in endoplasmic reticulum (ER) stress response in Arabidopsis. The cop1-4 mutant Arabidopsis plants were highly sensitive to ER stress induced by treatment with tunicarmycin (Tm). Interestingly, the abundance of nuclear-localized COP1 increased under ER stress conditions. Complementation of cop1-4 mutant plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, under prolonged treatment in seedlings, ABA-induced the nuclear translocation of COP1 and promoted salt stress tolerance by destabilising golden2-like1 protein to supress chloroplast development (Lee et al, 2021). Kang et al also reported that COP1 enhanced ER stress tolerance in Arabidopsis (Kang et al, 2021). It has also been reported that ACC treatment enhances COP1 nuclear localisation to promote hypocotyl elongation after 15 h of treatment in the light (Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, under prolonged treatment in seedlings, ABA-induced the nuclear translocation of COP1 and promoted salt stress tolerance by destabilising golden2-like1 protein to supress chloroplast development (Lee et al, 2021). Kang et al also reported that COP1 enhanced ER stress tolerance in Arabidopsis (Kang et al, 2021). It has also been reported that ACC treatment enhances COP1 nuclear localisation to promote hypocotyl elongation after 15 h of treatment in the light (Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The ecotype of plants used in all experiments was Arabidopsis thaliana Columbia‐0 (Col‐0). Mutants cop1‐4 (McNellis et al, 1994) and gi‐201 (Martin‐Tryon et al, 2007), along with transgenic lines 35S:COP1‐GFP/cop1‐4 (Lee et al, 2017), 35S:GI‐HA/gi‐2 (David et al, 2006), 35S:GI‐HA/cop1‐4 (Ahn et al, 2023), 35S:COP1 L105A ‐GFP/cop1‐4 , 35S:COP1 L170A ‐GFP/cop1‐4 and 35S:COP1 Cyt ‐GFP/cop1‐4 (Kang et al, 2021) used in this study have been previously described. Double mutants, gi‐201 cop1‐4 were obtained by genetic crossing, then verified by phenotypic inspection and Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The ecotype of plants used in all experiments was Arabidopsis thaliana Columbia-0 (Col-0). Mutants cop1-4 (McNellis et al, 1994) andgi-201 (Martin-Tryon et al, 2007), along with transgenic lines 35S:COP1-GFP/cop1-4 (Lee et al, 2017), 35S:GI-HA/gi-2 (David et al, 2006), 35S:GI-HA/cop1-4 (Ahn et al, 2023), 35S:COP1 L105A -GFP/cop1-4, 35S:COP1 L170A -GFP/cop1-4 and 35S:COP1 Cyt -GFP/cop1-4 (Kang et al, 2021)…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…ER stress response elements (ERSEs) are cis -acting DNA sequences in the promoter regions of genes targeted by UPR TFs [ 75 ], and the TF HY5 binds ERSEs preventing bZIP28 from binding and driving expression of downstream UPR genes [ 169 ]. COP1, an E3 ubiquitin ligase, relocates to the nucleus in ER stress, ubiquitinates HY5 and triggers its degradation, allowing bZIP28 to bind the ERSEs [ 169 , 170 ] ( Figure 4 ). Additionally, in mammalian cells experiencing chronic ER stress, ATF6 exhibits a reduction in its pro-life transcriptional activity due to SUMOylation in the nucleus likely operated by the E3 ligase PIAS1 [ 171 ].…”
Section: Ubiquitination and Ubl Modificationsmentioning
confidence: 99%